Barriers of School Transition for Children with Disability: Lived Experience of Parents in Kathmandu Valley - Baraily, Khagendra (Curriculum Development Journal, 2021)
This study aimed to explore the barrier of school transition for the children with disability from the parent's prospective. This study adopted qualitative method along with hermeneutics phenomenology. On the behalf of philosophical orientation, multiple realities were ontological basis and lived experiences of participants were epistemological assumption. The construct of critical disability theory was applied in this study. Purposefully 5 parents were selected from Kathmandu Valley. Data sources included field's notes, indepth interviews and artifacts. Interviewed data were transcribed and categorized to develop theme. Result revealed that several challenges such as awareness, attitude, accessibility, misconception, infrastructure, lack of policy implementation and ill motivation about disability are the major barrier towards transition. The perception of parents toward special school and rehabilitation centre are inadequately supporting to smooth transition. This study might be valuable support for policy maker in ensuring the no child left behind for the welfare state.